Pharmacological preconditioning with erythropoietin attenuates the organ injury and dysfunction induced in a rat model of hemorrhagic shock - Kiran K. Nandra; Massimo Collino; Mara Rogazzo; Roberto Fantozzi; Nimesh S. A. Patel; Christoph Thiemermann (The Company of Biologists, 2013)
SUMMARY Pre-treatment with erythropoietin (EPO) has been demonstrated to exert tissue-protective effects against 'ischemia-reperfusion'-type injuries. This protection might be mediated by mobilization of bone marrow endothelial progenitor cells (EPCs), which are thought to secrete paracrine factors. These effects could be exploited to protect against tissue injury induced in cases where hemorrhage is foreseeable, for example, prior to major surgery. Here, we investigate the effects of EPO pre-treatment on the organ injury and dysfunction induced by hemorrhagic shock (HS). Recombinant human EPO (1000 IU/kg/day i.p.) was administered to rats for 3 days. Rats were subjected to HS on day 4 (pre-treatment protocol). Mean arterial pressure was reduced to 35±5 mmHg for 90 minutes, followed by resuscitation with 20 ml/kg Ringer's lactate for 10 minutes and 50% of the shed blood for 50 minutes. Rats were sacrificed 4 hours after the onset of resuscitation. EPC (CD34+/flk-1+ cell) mobilization was measured following the 3-day pre-treatment with EPO and was significantly increased compared with rats pre-treated with phosphate-buffered saline. EPO pre-treatment significantly attenuated organ injury and dysfunction (renal, hepatic and neuromuscular) caused by HS. In livers from rats subjected to HS, EPO enhanced the phosphorylation of Akt (activation), glycogen synthase kinase-3β (GSK-3β; inhibition) and endothelial nitric oxide synthase (eNOS; activation). In the liver, HS also caused an increase in nuclear translocation of p65 (activation of NF-κB), which was attenuated by EPO. This data suggests that repetitive dosing with EPO prior to injury might protect against the organ injury and dysfunction induced by HS, by a mechanism that might involve mobilization of CD34+/flk-1+ cells, resulting in the activation of the Akt-eNOS survival pathway and inhibition of activation of GSK-3β and NF-κB.